FOREWARNED IS FOREARMED, MUTHI IN THE WORKPLACE: A REFLECTION ON NATIONAL SUGAR REFINING AND ALLIED INDUSTRIES UNION ON BEHALF OF MNGOMEZULU AND TONGAAT HULETT SUGAR LTD (2016) 37 ILJ 2441 (BCA) - Clarence Tshoose (Obiter, 2018)
The use of traditional medicine (muthi) is an integral part of the African culture. In fact, there is greater acceptance of the use of traditional medicine among Africans for health care purposes. Be that as it may, there are cases where traditional medicine is used for ulterior motives, such as witchcraft, causing harm, and casting a negative spell on other people. The aim of this case note is to look at the issue of dismissal arising from the use of traditional medicine and witchcraft in the workplace. This issue was examined in National Sugar Refining and Allied Industries Union on behalf of Mngomezulu and Tongaat Hulett Sugar Ltd (2016) 37 ILJ 2441 (BCA) (hereinafter “National Sugar Refining”). The note concludes with a discussion on whether the use of traditional medicine or witchcraft in the workplace constitutes a dismissable offence?